2001
DOI: 10.1128/jb.183.4.1242-1247.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genes Affecting Urease Activity inActinobacillus pleuropneumoniae

Abstract: Characterization of a series of urease-negative transposon mutations of Actinobacillus pleuropneumoniae revealed that many of the mutants had insertions 2 to 4 kbp upstream of the urease gene cluster. A 5-kbp upstream region of DNA was sequenced and found to contain six open reading frames (ORFs) transcribed in the same orientation as the urease genes. As well, a partial ORF, apuR, 202 bp upstream of these six ORFs, is transcribed in the opposite orientation. The predicted product of this partial ORF shows hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
3
43
1
Order By: Relevance
“…In two studies, cbiM, cbiQ, and cbiO genes were identified adjacent to bacte-rial urease genes (7,9) and were shown to be important for the urease activity in cells grown under nickel limitation.…”
mentioning
confidence: 99%
“…In two studies, cbiM, cbiQ, and cbiO genes were identified adjacent to bacte-rial urease genes (7,9) and were shown to be important for the urease activity in cells grown under nickel limitation.…”
mentioning
confidence: 99%
“…Examination of the urease gene cluster of the swine pathogen A. pleuropneumoniae (5) resulted in the identification and cloning of a putative urea transporter cDNA encoding a 300-amino acid protein ApUT (GenBank accession no. AAD49729).…”
mentioning
confidence: 99%
“…For several bacterial species in which nickel-transport systems were characterized, genes specifying these carriers were found within or in proximity to genetic loci encoding the nickel-requiring enzyme urease (1,2,19,26) or hydrogenase (13). In addition, nickel permeases of the ABC family are encoded by gene clusters which are harbored either on a plasmid (10), on a pathogenicity island (26), or adjacent to an insertion sequence (2,26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nickel permeases of the ABC family are encoded by gene clusters which are harbored either on a plasmid (10), on a pathogenicity island (26), or adjacent to an insertion sequence (2,26). In Y. pseudotuberculosis, ureH flanks the yut gene (30), located just downstream of the urease accessory gene ureD, whereas the yntABCDE polycistronic unit is upstream of the ureA structural urease gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation